Pharmacovigilance-based 12-year post-marketing safety analysis of quadrivalent influenza vaccines in children: a VAERS surveillance study - Fu, Honghong; Huang, Yirong; Wang, Xinjin; Zhang, Ying; Liu, Yijie; Su, Yonglong; Pan, Lili (Frontiers in Pediatrics, 2025)
BackgroundQuadrivalent influenza vaccines (QIVs) are extensively administered to children for seasonal influenza prevention. However, comprehensive long-term evaluations of post-marketing safety remain limited.MethodsWe conducted a comprehensive 12-year pharmacovigilance analysis utilizing data from the Vaccine Adverse Event Reporting System (VAERS) for individuals under 18 years receiving six FDA-approved QIVs between 2013 and 2024, representing three distinct platforms: four egg-based inactivated vaccines (Afluria, Fluarix, FluLaval, Fluzone), one cell culture-based inactivated vaccine (Flucelvax), and one live-attenuated intranasal vaccine (FluMist). Disproportionality analyses using reporting odds ratios (ROR) and Bayesian information component (IC) were employed to identify safety signals. Safety signals were considered statistically significant when the lower bound of the 95% confidence interval for ROR exceeded 1.0 and the lower bound of the IC (IC025) exceeded 0.ResultsOf the 15,458 reported adverse events, 5.29% (95% CI: 4.95–5.65) were classified as serious, including 67 fatalities. Guillain-Barré syndrome (GBS) emerged as a statistically significant safety signal (42 cases; ROR = 1.71, 95% CI: 1.25–2.35; IC025 = 0.28). Among specific QIV products, Flucelvax demonstrated the lowest proportion of serious adverse events (2.35%). Notably, reporting volumes decreased by 42% during the COVID-19 pandemic.ConclusionThis pharmacovigilance analysis demonstrates generally favorable safety profiles for pediatric QIVs, with cell culture formulations showing superior safety characteristics. The extremely low absolute risk of Guillain-Barré syndrome supports continued routine pediatric influenza vaccination while highlighting the importance of platform-specific safety monitoring.